Simple One-Medium Formulation Regeneration of Fingerroot Boesenbergia rotunda (L.) Mansf. Kulturpfl. via Somatic Embryogenesis - Tan, S.K.; Pippen, R.; Yusof, R.; Ibrahim, H.; Rahman, N.; Khalid, N. (2005)
Most published protocols necessitate different media formulations for multistep somatic embryogenesis. This study aims to establish a simple but effective formulation for the regeneration of plantlets of the pharmaceutically active Boesenbergia rotunda (L.) Mansf. Kulturpfl, formerly Boesenbergia/ Kaempferia pandurata (Schult), to ensure a superior and consistent supply of materials for commercialization purposes. In this study, a single-medium formulation of Murashige and Skoog (MS) supplemented with 13.54 μM 2,4-dichlorophenoxyacetic acid (2,4-D) was found to be the only medium out of eight formulations to promote the complete somatic embryogenesis process for the culture of B. rotunda (L.). Callus cultures were initiated from a total of 280 explants of rhizome meristem. The percentage of cultures forming embryogenic callus was 23.3 ± 4.3 on this MS medium augmented by 13.54 μM 2,4-D. The best plantlet regeneration rate was attained from the first subcultured callus with a mean of 6.6 ± 0.1 plantlets per 1 cm diameter aggregate of callus. Somatic embryogenesis characteristic of monocots was evident from histological studies. The regenerated plantlets have been successfully established in soil. © 2005 Society for In Vitro Biology.